Anisotropy of crystallite growth during sintering of SnO2 xerogels - Brito, G. E S [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Springer Nature, 1996)
The crytallite and pore-size evolution during isothermal sintering (400 ≤ T ≤ 700°C) of SnO2 xerogels was studied by X-ray line broadening and nitrogen adsorption-desorption isotherms. The experimental results show a strong anisotropy of crystallite growth between [110] and [101] directions. The preferential growth at [101] is followed by an increase in the mean pore size, reduction of the specific surface area and invariance of total pore volume. This behaviour is typical of grain coalescence sintering. The kinetic analysis of experimental results suggests that the crystallite coalescence at [101] is governed by lattice diffusion. The strong anisotropy of the growth causes pore-size distribution broadening, hindering the macroscopic shrinkage of the compact during sintering. © 1996 Chapman & Hall.
Keywords: Adsorption; Anisotropy; Coalescence; Crystal growth; Crystal lattices; Desorption; Diffusion; Kinetic theory; Reduction; Shrinkage; Sintering; Crystallite growth; Grain coalescence sintering; Isothermal sintering; Nitrogen adsorption desorption isotherms; Pore size distribution; Specific surface area; X ray line broadening; Xerogels; Gels